ANALISA SENYAWA METABOLIT SEKUNDER DAN PENGARUH PEMBERIAN SERBUK SEMUT JEPANG TERHADAP KADAR KOLESTEROL PADA TIKUS PUTIH JANTAN - Evi Ekayanti Ginting; Cindy Fatika Sari; Leny Leny; Parhan Parhan; Pricella Ginting (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
This study aimed to examine the anticholesterol activity of Japanese ant powder on male white rats of the Wistar strain. This research was conducted experimentally with the method of pre-test and post-test with control group design. The negatif control was given Na-CMC 1%, the positive control was simvastatin 10 mg/kgBW, and the Japanese ant powder treatment group was given a dose of 100 mg/kgBW, 200 mg/kgBW and 300 mg/kgBW. The treatment of rats was given orally. Total cholesterol levels were measured in rat blood serum by the enzymatic CHODPAP method. Measurement of total cholesterol levels was carried out on the 15th and 22nd days using a microlab 300 photometer. The results showed that Japanese ant powder had anticholesterol activity. The percentage of cholesterol reduction in positive control was 59.75%, Japanese ant powder dose of 100 mg/kgBW was 41.79%, dose of Japanese ant powder 200 mg/kgBW was 48.72% and 300 mg/kgBW was 53.83%. The results of the ANOVA test showed a significant difference with a p value <0.05. The conclusion of this study is that Japanese ant powder has activity in reducing cholesterol levels in male white rats and the effective dose is 300 mg/kgBW.